Selective activation of the c-Jun N-terminal kinase (JNK) pathway fails to elicit Bax activation or apoptosis unless the phosphoinositide 3′-kinase (PI3K) pathway is inhibited - Molton, Sarah A; Todd, Daniel E; Cook, Simon J (Oncogene, 2003)
c-Jun N-terminal kinase (JNK) is activated when cells are exposed to noxious stimuli. The role of JNK in apoptosis is subject to considerable debate; for example, JNK activation may promote or inhibit apoptosis depending on the cell type and stimulus involved. These conflicting results have arisen in part because few studies have successfully separated JNK activation from the primary stress-induced damage or from other stress-induced signalling pathways. Here we describe a conditional mutant, ΔMEKK1:ER*, which allows selective activation of the JNK cascade in the absence of any cellular stress. Activation of ΔMEKK1:ER* in CC139 fibroblasts resulted in the rapid and sustained activation of JNK without activating ERK or p38 or promoting I κ B α phosphorylation. Activation of ΔMEKK1:ER* caused a reversible halt in cell growth but failed to induce apoptosis. In contrast, treatment of cells with LY294002, to inhibit phosphoinositide 3-kinase (PI3K), caused downregulation of Bcl-2 and Mcl-1 and allowed ΔMEKK1:ER* to elicit a robust apoptotic response characterized by activation of Bax and caspases. This PI3K-inhibitable, JNK-induced death response was not impeded, but actually accelerated, by cycloheximide. This suggests that JNK-induced activation of Bax and cell death does not require the upregulation of pro-death genes such as Bim or FasL, but rather proceeds through pre-existing components. However, if the PI3K cell survival pathway is not inhibited, even sustained activation of JNK exerts no overt proapoptotic effect in CC139 cells.